Epitaxial growth of AlN films on sapphire via a multilayer structure adopting a low- and high-temperature alternation technique. Issue 39 (12th August 2015) - Zhang, X.; Xu, F. J.; Wang, J. M.; He, C. G.; Zhang, L. S.; Huang, J.; Cheng, J. P.; Qin, Z. X.; Yang, X. L.; Tang, N.; Wang, X. Q.; Shen, B.
Abstract : Epitaxial growth of AlN films on c -sapphire using a multilayer structure has been investigated by metal–organic chemical vapor deposition adopting multiple alternation cycles of low- and high-temperature (LT–HT) growth. Abstract : Epitaxial growth of AlN films on c -sapphire using a multilayer structure has been investigated by metal–organic chemical vapor deposition adopting multiple alternation cycles of low- and high-temperature (LT–HT) growth. It is found that the surface morphology and crystal quality can be greatly improved using three alternation cycles with X-ray diffraction ω -scan full width at half maximum values of 311 and 548 arcsec for the (0002) and (10−12) peaks, respectively, which are induced by the alternation of the three-dimensional (3D) and two-dimensional (2D) growth modes caused by the LT–HT process. The first 3D–2D cycle is found to play a major role in threading dislocation reduction, while the second and third cycles mainly account for tensile stress relaxation.